Utilization of public health care by people with private health insurance: a systematic review and meta-analysis - Congcong Zhang; Chenwei Fu; Yimin Song; Rong Feng; Xinjuan Wu; Yongning Li (BMC, 2020)
Abstract Background The objective of this systematic review was to explore the association between private health insurance and health care utilization. Methods We searched the MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL) electronic databases for relevant articles since 2010. Studies were eligible if they described original empirical research on the utilization of public health care by individuals with private health insurance, compared with individuals without private insurance. A pooled measure of association between insurance status with health care utilization was assessed through meta-analysis. Results Twenty-six articles were included in the final analysis. We found that patients with private insurance did not use more public health care than people without private insurance (P < 0.05). According to the subgroup analysis, people with private insurance were more likely to be hospitalized than people with no insurance (OR 1.67; 95% CI, 1.18 to 2.36). Conclusions People with private insurance did not increase their use of health care (outpatient services), compared to those without private insurance. Private health insurance coverage may ease the financial burden on patients and on the public health insurance system.